PERAN PEMBELAJARAN KALIGRAFI DALAM KETERAMPILAN MENULIS ARAB PADA MATA PELAJARAN AL-QUR’AN HADITS SISWA KELAS VIII C DI MTS DARUL ULUM SUKARAJA KEC. LOGAS TANAH DARAT - Badriah Badriah; Andrizal Andrizal; A Mualif (Universitas Islam Kuantan Singingi, 2022)
This research is motivated by the importance of good and correct Arabic writing skills. Based on what the researchers did in class VIII C Mts Darul Ulum Sukaraja Kec. Logas Tanah Darat, found the following problems: Calligraphy learning has been studied but the students' writing is still not neat, Not neatly arranged, the letters are not visible above the line and below the line, There are still errors in writing Arabic letters . This research includes qualitative research. The subjects in this study were 1 Calligraphy Subject Teacher, 1 Al-Qur'an Hadith Teacher and 38 Class VIII C students at MTs Darul Ulum Sukaraja. In data collection techniques, namely interviews, observation and documentation. Data analysis techniques using Miles and Huberman techniques include: data reduction, data presentation, and drawing conclusions. Based on the results of the study, it was found that: learning calligraphy plays a very important role in students' Arabic writing skills, namely helping to improve students' Arabic writing to be neater and more correct, so that students can get used to writing the Al-Quran and Hadith well, and can practice patience, patience, thoroughness and neatness. student.